Raw-material-intensive Economy and Development of Small and Medium-sized Enterprises in Kazakhstan - Kurmanov, Nurlan; Beisengaliyev, Berik; Dogalov, Amangeldy; Turekulova, Dametken; Kurmankulova, Nurzhamal (International Journal of Economics and Financial Issues, 2016)
Kazakhstan’s economy is growing in unstable dynamics and is still oriented on the mining industry. The purpose of the study is to determine the structure of the economy and to present an overview of the development and current status of small and mediumâ€sized enterprises in Kazakhstan. Research was composed to measure variation in the economic development in Kazakhstan required in times of increasing global competition. Keywords: Raw-Material-Intensive Economy, Small and Medium-sized Enterprises, Kazakhstan. JEL Classifications: H89, M13